Implementasi Pendidikan Multikultural pada Anak-Anak Melalui Model Pembelajaran Bermain Peran (THUFULA, 2016)
Multicultural education is very important to be applied in Indonesia. This is motivated by several reasons, one of them is globalization. Globalization gives rise to opportunities, threats and challenges to human life. One impact is the nation's culture. Nations are not able to manage the diversity will experience a loss of local and national identity.Multicultural education is a strategy in offering a powerful strategy of cultural transformation through education that is able to appreciate cultural differences.One of strategy to teach Multicultural Education is through role play. Children can play the roles chosen by the teacher.In a role-play, the teacher can teach a wide range of vocabulary, traditional clothes, traditional house, and folk songs. Children will also feel happy when playing a certain role. Keywords: Multicultural Education, Role Playing, Kids                 ABSTRAK Pendidikan Multikultural sangat penting untuk diterapkan di Indonesia. Hal ini dilatarbelakangi oleh beberapa sebab, salah satunya adalah globlalisasi. Globlaisasi melahirkan peluang, ancaman, dan tantangan bagi kehidupan manusia. Salah satu imbasnya adalah kebudayaan bangsa. Bangsa yang tidak mampu mengelola kemajemukan akan mengalami kehilangan jati diri lokal dan nasionalnya.Pendidikan Multikultural merupakan strategi dalam menawarkan strategi transformasi budaya yang ampuh melalui pendidikan yang mampu menghargai perbedaan budaya.Salah satu cara untuk mengajar Pendidikan Multikultural adalah melalui bermain peran. Anak-anak dapat memainkan peran-peran yang dipilihkan oleh gurunya.Dalam bermain peran, guru dapat mengajarkan berbagai kosa kata, pakaian daerah, rumah istiadat, dan lagu daerah. Anak-anak juga akan merasa senang ketika memainkan peran tertentu. Kata Kunci: Pendidikan Multikultural, Role Playing, Anak-anak